The issue of urban public space in age of “investor urbanism” - Penčić, D. and Lazarevski, S. (Faculty of Civil Engineering - Subotica, University of Novi Sad, 2020)
By reviewing the current condition of urban public space in recent decades, the paper explains the relationship between current urban planning priorities and the changes that are taking place in cities due to them. The research was conducted in part of the city of Skopje, more precisely on the territory of the municipality of Centar, as the most prominent example of the situation. Skopje from a city with a rich history of socialist urbanism and a laboratory of progressive modernist ideas for a city, in the long transition period loses its most pronounced quality - the wealth of open public spaces. Changing the goals of urban planning and giving priority to economic demands, expressed through the need to fill the budget of local self-government and the demands of investors for intensive construction, are key in changing the attitude towards open public space, most pronounced as a reduction in volume and quality.
Keywords: urban planning, open public space, “investor urbanism”